PROSPEK AGROINDUSTRI SAGU DI SUMATERA BARAT KHUSUSNYA DI KEPULAUAN MEBNTAWAI - Gusmailina Gusmailina (Jurnal Penelitian Hasil Hutan, 1992)
The potential of sago forest  in Menlawai lslands has not yet been optimally exploited either as raw materia for  industry and as food sources.  This article  is based on survey  carried out in Mentawai islands, Wert Sumatera, on June  1991.40 %  of Mentawm lsland are swamps  and peals which the only possible exploitation of the area is through sago cultivation, that will produce sago as raw material for agroindustry.sago is abundantly avaiqble in the Mentawai Islands.  Since man power and market, are no longer a problem, it is expected that sago industry  would have a good prospect in the future.The lslands could pioneer  the  improvement of  sago processing from  traditional method  to  a  relatively  modern  way.  Hence,  indirectly it would speed up the rate of economic development in the area.